An Emerging Role for Prolactin in Female-Selective Pain. Issue 8 (August 2020) - Chen, Yanxia; Navratilova, Edita; Dodick, David W.; Porreca, Frank
Abstract : Women experience many pain conditions more frequently when compared with men, but the biological mechanisms underlying sex differences in pain remain poorly understood. In particular, little is known about possible sex differences in peripheral nociceptors, the fundamental building blocks of pain transmission. Emerging evidence reveals that prolactin (PRL) signaling at its cognate prolactin receptor (PRLR) in primary afferents promotes nociceptor sensitization and pain in a female-selective fashion. In this review, we summarize recent progress in understanding the female-selective role of PRL/PRLR in nociceptor sensitization and in pathological pain conditions, including postoperative, inflammatory, neuropathic, and migraine pain, as well as opioid-induced hyperalgesia. The clinical implications of the peripheral PRL/PRLR system for the discovery of new therapies for pain control in women are also discussed. Highlights: Women display a higher prevalence of many pain conditions, suggesting a role for sexually dimorphic pain mechanisms. Emerging evidence implicates the prolactin (PRL) and prolactin receptor (PRLR) system as a female-selective mechanism promoting pain in females. PRL signals differentially through long and short PRLR (PRLR-L and PRLR-S) that reciprocally inhibit PRL signaling. Increased nociceptor excitability and pain result from PRL signaling through PRLR-S. Dysregulation of PRLR isoforms in pathological states may provide a basis for female-prevalent pain disorders, and allow the development of therapeutic strategies for improved treatment of pain in women.